2013
DOI: 10.1038/mi.2012.116
|View full text |Cite
|
Sign up to set email alerts
|

The adult penile urethra is a novel entry site for HIV-1 that preferentially targets resident urethral macrophages

Abstract: The penile urethra is routinely targeted by sexually transmitted bacterial and viral pathogens, and also represents a probable site for HIV type-1 (HIV-1) entry. Yet, the mechanisms of urethral HIV-1 transmission are unknown. To describe the initial steps of penile HIV-1 entry, we obtained whole penile tissues from individuals undergoing elective gender reassignment and developed ex vivo polarized explants of different penile epithelia, as well as in vitro immunocompetent reconstructed urethra. In penile expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 37 publications
7
87
0
6
Order By: Relevance
“…We evidenced the presence of SIV RNA ϩ macrophages in the urethra from HAART-treated macaques with reduced or undetectable viremia. In agreement with our findings in macaques in vivo, the preferential infection of resident macrophages was recently described in human urethral tissue exposed ex vivo to HIV-1 (87). It was recently suggested that myeloid cells in the gut and lymphoid tissues from SIV-infected primates are resistant to infection and acquire SIV DNA primarily through the phagocytosis of infected T cells (90).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We evidenced the presence of SIV RNA ϩ macrophages in the urethra from HAART-treated macaques with reduced or undetectable viremia. In agreement with our findings in macaques in vivo, the preferential infection of resident macrophages was recently described in human urethral tissue exposed ex vivo to HIV-1 (87). It was recently suggested that myeloid cells in the gut and lymphoid tissues from SIV-infected primates are resistant to infection and acquire SIV DNA primarily through the phagocytosis of infected T cells (90).…”
Section: Discussionsupporting
confidence: 81%
“…Such a high number of macrophages was also reported for the urethra from healthy uninfected men (87)(88)(89). The majority of T lymphocytes in macaques' urethras were CD4 negative, as previously reported for human urethral tissue (87,88). We evidenced the presence of SIV RNA ϩ macrophages in the urethra from HAART-treated macaques with reduced or undetectable viremia.…”
Section: Discussionmentioning
confidence: 64%
“…In the first, explants of foreskin, glans, meatus, and urethra were found susceptible to infection with HIV-1 BaL, an R5-tropic strain (Anderson et al 2011). In the second, urethral macrophages were susceptible to infection with cell-associated HIV-1 (Ganor et al 2013). Thus, these studies confirm the infectability of sites other than the foreskin within the male RT.…”
Section: Male Reproductive Tractsupporting
confidence: 60%
“…Aside from cell-to-cell HIV-1 transmission, trans infection may play a critical role in the propagation of sexual transmission of HIV-1 (Bobardt et al, 2007; Bomsel, 1997; Devito et al, 2000; Ganor et al, 2013; Gupta et al, 2013; Kinlock et al, 2014; Kohli et al, 2014; Saidi et al, 2007). To determine whether SE are capable of eliciting a block on HIV-1 trans infection, we utilized a trans well chamber system.…”
Section: Resultsmentioning
confidence: 99%